Mathematical Model of the Influence of Innovative Development Factors on the Economy of Leading Countries and Russia - A. Rodionova, I.; V. Kokuytseva, T.; S. Semenov, A. (International Journal of Engineering and Technology, 2018)
This article is dedicated to the econometric analysis of the influence of different factors on the economic development. It has been proved that the gross domestic product is under the influence of exogenous variables such as value added of knowledge and technology intensive industries (KTI), number of patents granted in smart grid technology and expenditures on R&D. Creation of econometrical models provides an empirical evidence to support the evaluation of economic relationships, which occur in a modern economy in the era of development of digital technologies.The penetration of information and communication technologies (ICT) into all sectors of the economy and the sphere of vital activity of the population is a key factor of scientific, technical and economic progress in the context of globalization. Opportunities and difficulties of the countries of the world in the transition to a post-industrial economy reflect international ratings. They characterize the unevenness of innovative development and the use of innovations and information technologies. For the analysis of Russia's positions in the world innovation economy, several international ratings of innovative development have been selected (The Global Innovation Index, The Networking Readiness Index, and The Global Competitiveness Index). The analysis showed not only the representativeness of the international innovation ratings chosen for the analysis, but also the high correlation between the indices in international innovation ratings and individual indicators of economic development of countries. The importance of policies in the use of ICT and the digital economy for structural changes in the economy is noted.Russia is inferior to the world's leading leaders in terms of innovation activity and economic development. In the light of the economic sanctions of the economically developed countries of the West against Russia, this gap may even increase. Assessing Russia's position in international innovation development ratings, including R & D spending, has highlighted the need to take into account global trends and challenges, and econometric analysis helps to understand the world trends better and to offer reasonedÂ  recommendations for improving the situation in this area.The recommendations will facilitate Russia's early transition to a socially-oriented innovative type of economic development. The main direction is the development of the national innovation system and the inclusion of Russia in the global innovation space.The purpose of this research is to describe mathematically the influence of modern innovative factors on economy on the example of one of the leading countries, to characterize Russia's position in international innovation ratings and highlight Russia's problems in research and innovation. Results and practical importance are to issue recommendations for improving the activation of Russia's involvement in the process of internationalization in the field of research and innovation. It is necessary to adjust the direction of further development.Â Â